2015
DOI: 10.1093/infdis/jiv252
|View full text |Cite
|
Sign up to set email alerts
|

Serum Procalcitonin Measurement and Viral Testing to Guide Antibiotic Use for Respiratory Infections in Hospitalized Adults: A Randomized Controlled Trial

Abstract: NCT01907659.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 34 publications
4
103
2
Order By: Relevance
“…However, a number of previous studies have shown that patients with viral diseases had PCT levels <0.5 ng/mL [37,38]. In our study, PCT ≥0.7 ng/mL was independently associated with dengue shock and/or organ failure.…”
Section: Discussioncontrasting
confidence: 44%
“…However, a number of previous studies have shown that patients with viral diseases had PCT levels <0.5 ng/mL [37,38]. In our study, PCT ≥0.7 ng/mL was independently associated with dengue shock and/or organ failure.…”
Section: Discussioncontrasting
confidence: 44%
“…The PSI score [18] had also been used in that cohort to classify patients according to severity. For comparability with our study group, we selected only patients with PSI risk classes I and II who met the inclusion/exclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of PCT monitoring in patients with LRTIs was studied in a variety of randomized controlled trials, mainly in the inpatient setting (Table ). Overall, studies in this patient population demonstrated that PCT monitoring, when compared with standard care (no PCT monitoring), results in a reduction in antibiotic therapy duration in the range of 0–8 days, with no corresponding impact on infection relapses . A large meta‐analysis detected a significant reduction in 30‐day mortality in patients with acute respiratory infections receiving PCT‐guided therapy compared with those receiving standard care (9% vs 10%; adjusted OR 0.83, 95% CI 0.70–0.99, p=0.37, respectively) .…”
Section: Procalcitonin As a Determinant Of Antibiotic Therapy Durationmentioning
confidence: 87%
“…The authors cited modest adherence and lack of serial PCT measurements as potential factors contributing to the lack of observed benefits. In other studies, adherence to PCT algorithms varies greatly, ranging from 47–97% …”
Section: Challenges Implementing Pct Monitoringmentioning
confidence: 98%